TINDAK TUTUR DALAM PROSES JUAL BELI DI PASAR TRADISIONAL SURAKARTA - Ririn Linda Tunggal Sari; Sumarlam Sumarlam; Dwi Purnanto (Universitas Sebelas Maret, 2016)
The objectives of this research are: to describe the forms of speech acts and to show the most dominant speech act and the reasons of its use; and to describe and define the politeness principle found in the the goods sale and purchase process at traditional markets in Surakarta.This research used the descriptive qualitive method with the pragmatics approach. Its sources were conversations or dialogues. The data of the research were utterances and their contexts which contain speech acts and which apply the cooperative principle in the goods sale and purchase process at traditional markets in Surakarta, namely: Pasar Gedhe market, Pasar Klewer market, Pasar Ledoksari market, Pasar Nusukan market, and Pasar Mojosongo market. The collection of the data used the listening method. The data were collected through tapping, uninvolved conversation observation, recording technique, and note-taking techniques. They were analyzed by using the means-end techique. The result of the analysis was presented with informal and formal methods.There are five types of speech act employed by the sellers and the buyers to express their intentions, namely: utterances, (b) verdictive utterances, (c) directive utterances, (d) commissive utterances, and phatic utterances. The most dominant speech act used in the goods sale and purchase process at traditional markets in Surakarta is commisive utterances as indicated by 88 data. In relation to the cooperative principle, in the goods sale and purchase process at traditional markets in Surakarta some speech acts adhere to the cooperative principle, but some violate it. The adherence to and violence of the cooperative principle are balanced in term of frequency i.e. 95 data for each. The latter is due to the intentions of the sellers and the buyers to show their politeness.There are applications of the speech act theory, the cooperative principle, and the politeness in the dialogues between the sellers and the buyers in the the goods sale and purchase process at traditional markets in Surakarta Keywords: Speech act, cooperative principle, sale and purchase process, pragmatics